Virtual Reality System for Inspection and Training in Wheel Loader - Oliveira, Taina Ribeiro de; Gomes, Guilherme Iglesias Rocha; Martins, Thiago Silva; Borges, Luiz Felipe Muniz Rocha; Ludke, Gabriel Giesen; Andreao, Rodrigo Varejao; Cotini, Luan Guio; Viana, Pedro Henrique Porto; Schimidt, Marchelo Queiroz; Mestria, Mario (Anais do Simpósio de Realidade Virtual e Aumentada (SVR), 2022)
In this study, a simulator is proposed for inspection and training of a wheel loader based on a first-person serious game and virtual reality. The simulator was developed using a cross-platform game engine and integrated into various virtual reality headsets. The goal of the game was to conduct maintenance inspection procedures on the wheel loader of a mining company. A group of 34 users tested the simulator and completed a survey. The results showed that the system is suitable for inspection and training of staff before they can use a real wheel loader at a mining company. The findings revealed that implementing a simulator for inspection and maintenance training can enhance the process, reducing expenses and increasing safety. In addition, methods in the real-world of training are scarcely sufficient to instruct operators in all dangerous situations. These methods are generally effective, but they do not give operators the real-life impression of all scenarios. In this sense, the serious game makes the training effective because it gives operators a sense of realism. Beyond, the simulator can be extended to include other types of procedures with several situations.